Screening of Cucumber Fusarium Wilt Bio-Inhibitor: High Sporulation Trichoderma harzianum Mutant Cultured on Moso Bamboo Medium - Zhang, Ning; Xu, Hao; Xie, Jingcong; Cui, Jie-yu; Yang, Jing; Zhao, Jian; Tong, Yajuan; Jiang, Jianchun (Frontiers in Microbiology, 2021)
Cucumber fusarium wilt is a soil-borne disease which causes serious production decrease in cucumber cultivation world widely. Extensive using of chemical pesticides has caused serious environmental pollution and economic losses, therefore, it is particularly urgent to develop efficient, safe and pollution-free biopesticide. In this study, a mutant strain of Trichoderma harzianum cultivated in moso bamboo medium was proved to be an efficient bio-inhibitor of the disease. The mutant strain T.harzianum T334, was obtained by three microwave mutagenesis cycles with an irradiation power of 600 W and irradiation time of 40 seconds. In contrast to the original strain, the inhibition rate on cucumber fusarium wilt of the strain T334 increased from 23.81% to 78%. In this work, disc milling pretreatment of moso bamboo has shown significant beneficial effects on both biotransformation and sporulation of T334. Its sporulation reached 3.7×109 cfu/g in mushroom bags with 90% bamboo stem powder (pretreated by disc milli), 9.5% bamboo leaf powder and 0.5 % wheat bran when the ratio of solid to liquid was 4:6, the inoculum amount was 10%, and the culture temperature was 28 ℃. These results provide an alternative bioinhibitor for the control of cucumber fusarium wilt, and a potential usage of moso bamboo in the production of microbial pesticide.